Narrative Theology in the High School Classroom: Teaching Theology Through the Literature - DelFra, CSC, Louis A. (Catholic Education: A Journal of Inquiry and Practice, 2005)
If Jesus Taught most Frequently through symbol and story, and the early Church passed on his teachings primarily through story, especially the four Gospels, why is today’s Catechesis and theological pedagogy not more informed by “narrative theology” ”“ theology which focuses on the narratives told by Jesus and the Gospels precisely as narratives? This article provides some basic foundations for the discipline of narrative theology, argues for a more narrative approach to theological instruction, and, by way of application, proposes a full year curriculum for high-school students that enables teachers to teach theology through the narratives of both the Bible and secular literature.